(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The most common form of bladder cancer is transitional cell carcinoma (developing from the transitional epithelium of the urinary tract), less common are squamous cell carcinoma and adenocarcinoma (a tumor derived from and built from the glandular epithelium). The main methods for diagnosing RMP are cystoscopy with biopsy. Modern radiological imaging helps to plan the treatment of localized kidney cancer, allowing the characterization of volumetric lesions. A CT-based radiomics prediction model can assess the muscle invasiveness of bladder cancer before surgery with good diagnostic performance. Bladder cytology gives the highest specificity and the NMP22 BladderChek urine marker test the highest sensitivity for high-grade tumors. Their combination appears to be the best approach for susceptibility to high-grade tumors compared to single markers and other combinations.